Synthesis, Characterization, and Antioxidant Studies of Novel Cu(II) and Ni(II) Homo Binuclear Complexes with N,N’-bis(Benzamidothiocarbonyl) Hydrazine Ligand Derivatives - Abdulmanaf, Huner S.; Meena, Bashdar I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
This study presents the synthesis, spectral characterization, and antioxidant evaluation of Cu(II) and Ni(II) homo binuclear complexes derived from three bis(thiourea)hydrazine ligands: N, N′-bis(benzamidothiocarbonyl)hydrazine (L1), N, N′-bis(o-chlorobenzamidothiocarbonyl)-hydrazine (L2), and N, N′-bis(p-methylbenzamidothiocarbonyl)hydrazine (L3). The ligands were synthesized via condensation reactions and characterized using CHNS elemental analysis, FT-IR, UV-Vis, and ¹H NMR and ¹³C NMR spectroscopy. The metal complexes were prepared in a 2:1 metal-to-ligand molar ratio and characterized by melting point determination, magnetic susceptibility, molar conductivity, and spectral techniques. IR data confirmed coordination through the thiocarbonyl sulfur and amide oxygen atoms, forming neutral bidentate complexes. Magnetic moment values and electronic spectra were consistent with square planar geometries for both Cu(II) and Ni(II) complexes. Molar conductance measurements indicated non-electrolytic behavior in DMF. Antioxidant activity was assessed via the DPPH radical scavenging assay, revealing that the metal complexes exhibited enhanced radical scavenging capacity compared to the free ligands, likely due to increased delocalization and metal ion involvement in electron transfer. These findings highlight the potential of bis(thiourea)hydrazine-based metal complexes as antioxidant agents.